2016
DOI: 10.1038/srep35927
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of codon usage patterns in Ginkgo biloba reveals codon usage tendency from A/U-ending to G/C-ending

Abstract: As one of the most ancient tree species, the codon usage pattern analysis of Ginkgo biloba is a useful way to understand its evolutionary and genetic mechanisms. Several studies have been conducted on angiosperms, but seldom on gymnosperms. Based on RNA-Seq data of the G. biloba transcriptome, amount to 17,579 unigenes longer than 300 bp were selected and analyzed from 68,547 candidates. The codon usage pattern tended towards more frequently use of A/U-ending codons, which showed an obvious gradient progressin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
59
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(73 citation statements)
references
References 53 publications
14
59
0
Order By: Relevance
“…If there exists a significant correlation ( p = .01 or .05) between GC12 and GC3, it indicates that directional mutation pressure plays the key role in the CUB of these genes. In addition, whenever regression coefficient value approaches to “0,” it indicates that natural selection plays a key role in the CUB of genes; conversely, when the value of regression coefficient is close to “1,” it indicates mutation pressure plays a key role in the CUB of genes under study …”
Section: Materials and Methodologymentioning
confidence: 99%
See 2 more Smart Citations
“…If there exists a significant correlation ( p = .01 or .05) between GC12 and GC3, it indicates that directional mutation pressure plays the key role in the CUB of these genes. In addition, whenever regression coefficient value approaches to “0,” it indicates that natural selection plays a key role in the CUB of genes; conversely, when the value of regression coefficient is close to “1,” it indicates mutation pressure plays a key role in the CUB of genes under study …”
Section: Materials and Methodologymentioning
confidence: 99%
“…In addition, whenever regression coefficient value approaches to "0," it indicates that natural selection plays a key role in the CUB of genes; conversely, when the value of regression coefficient is close to "1," it indicates mutation pressure plays a key role in the CUB of genes under study. 19…”
Section: Neutrality Plotmentioning
confidence: 99%
See 1 more Smart Citation
“…The number of raw CDSs of six Euphorbiaceae species was 85, 84, 84, 83, 86 and 85 respectively (Table 1; Table S1). In order to avoid sampling errors, each CDS in the chloroplast genomes of six Euphorbiaceae species should follow certain rules, i.e., the number of bases in each CDS should be the fold of three; the length of sequence encoding gene must be ≥ 300 bp; high-quality sequences with identified bases, i.e., containing only A, T, G and C bases; each CDS contains proper initiation codon (ATG) and termination codons (TAG,TGA and TAA); and sequences without an intermediate stop codon (He et al, 2016;Li et al, 2016;Zhang et al, 2007). We used Perl scripts written by our team to filter the CDSs according to the five rules mentioned above and simplify the names of CDSs replaced with numbers to avoid miscalculation.…”
Section: Genomes and Coding Sequencesmentioning
confidence: 99%
“…We summarized the recent progresses of codon bias (codon optimality) and its selection patterns in plants. A study in the ancient gymnosperm species Gingko biloba found higher frequency for A/T ending codons than G/ C ending codons, but meanwhile it found that the highly expressed genes and those genes involved in environmental adaptation tend to use C/G ending codons, suggesting that the Gingko genome is dominated by natural selection [9]. Similarly, in angiosperms, it was found that the G/C ending codons were optimal (e.g.…”
Section: Introductionmentioning
confidence: 99%